Deleuzian Vitalism and its Discontents - K. S, Arsh (Cosmos and History: The Journal of Natural and Social Philosophy, 2025)
What I have tried to do with this paper is to present Bergson as Deleuze takes him up as an inspiration. This was done to depict what Deleuze builds on in his philosophy, namely the topic of difference and differentiation. This fed into an examination of Deleuze’s critique of the dialectic as evinced in ‘Nietzsche and Philosophy’. I then sought to present a preliminary response from the dialectician’s camp via an account of Althusser and his concept of 'determination in the last instance' which in my view answers to an extent the charge that Deleuze levels against dialectics (that it is unable to think the singular determinative principle in an encounter or multiplicity). Subsequently I represent Deleuze’s deeper problem that is his critique of representation itself, and specify that his real target in critiquing the dialectic is Hegel. This warrants a brief look at Hegel and the process of negation that his dialectic enters into which is very much what Deleuze wants to distance his art of concept creation from. In what a possible alternative to Hegelian negation may be, I present Bergson’s examination of aesthetic sense or beauty and its suggestiveness as an example. In way of a response I try and show how Hegelian expressive causality as depicted by Althusser is also capable of representing aesthetic and political relations and perhaps in a more determinate manner. I end with presenting Žižek more contemporary critique of Deleuze.